Representación de la juventud, niñez y adolescencia en el cine ecuatoriano, periodo 2014 – 2024. - Aguagallo Suárez, Astrid Arianna (2026)
This research paper explores the representation of childhood, youth, and adolescence in contemporary Ecuadorian cinema through a narrative and symbolic analysis of a selection of national films produced since the early 21st century. It identifies patterns in the construction of subjectivities, sociocultural discourses, and aesthetic strategies that reveal both structural tensions and processes of child and youth agency. The study argues that these representations not only reproduce social realities but also question and re-signify them.